The Big Bang of Originality and Effectiveness: A Dynamic Creativity Framework and Its Application to Scientific Missions - Corazza, Giovanni Emanuele; Lubart, Todd (Frontiers in Psychology, 2020)
This article introduces a theoretical framework to conceptualize the dynamics of the phenomenon of creativity, which is then applied to the specific case of scientific missions for the exploration of the universe. Static definitions of creativity are insufficient for this purpose, as they fail to describe states of creative inconclusiveness as well as the time and culture-dependent estimation of the value of the outcomes of a creative process; therefore, a dynamic definition of creativity is introduced, justified, and adopted to build a dynamic creativity framework. Within this framework creativity episodes are shown to be mutually interconnected through several mechanisms (past and future concatenation, estimation, exaptation), to form a dynamic universal creativity process (DUCP), the beginning of which can be traced back to the Big Bang of our universe. The DUCP entails several layers of complexity (material, biological, sociocultural, artificial), showing that creativity is not only a psychological construct for humans, but rather a unifying cosmological principle. Context embeddedness is discussed in depth, introducing a taxonomy based on the concepts of tightness and looseness as applied to conceptual space and time. This theoretical framework is then applied to the discussion of the design, realization, and operations of scientific missions for the exploration of the universe, taking as a reference the terminology adopted by the European Space Agency.